The Influence of Career Development, Competence and Work Conflict on Job Satisfaction - Seno, Seno; Magito, Magito; Perkasa, Didin Hikmah (Talent: Journal of Economics and Business, 2023)
Job satisfaction is a description of an employee's feelings of pleasure and displeasure with the work he does, by identifying the results of the work that has been done, supervisor recognition of the work that has been done, compensation, self-development, supervision of superiors and the relationship of the employee's emotional state that occurs or does not occur the meeting point between the value of the employee's work and the company or organization with the level of return value that the employee concerned really wants. This study aims to determine and analyze the effect of Career Development, Competence and Job Conflict on Job Satisfaction (Case Study at Wisma Lampung Jakarta Service Unit). The research design uses a causal quantitative method, namely knowing the effect between the variables studied. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via googleform. The population studied in this study were 50 people, using saturated sampling techniques. Data analysis was carried out using Smart-PLS (Partial Least Square) through outer model testing, inner model and hypothesis testing. The results showed that the career development variable had an effect on job satisfaction, the competency variable had an effect on job satisfaction and work conflict had an effect on job satisfaction in the Wisma Lampung Jakarta Service Unit.